Cystatin C in Alzheimer's disease - Levy, Efrat (Frontiers in Molecular Neuroscience, 2012)
Changes in expression and secretion levels of cystatin C (CysC) in the brain in various neurological disorders and in animal models of neurodegeneration underscore a role for CysC in these conditions. A polymorphism in the CysC gene (CST3) is linked to increased risk for Alzheimer’s disease (AD). AD pathology is characterized by deposition of oligomeric and fibrillar forms of amyloid β (Aβ) in the neuropil and cerebral vessel walls, neurofibrillary tangles, and neurodegeneration. The implication of CysC in AD was initially suggested by its co-localization with Aβ in amyloid-laden vascular walls, and in senile plaque cores of amyloid in the brains of patients with AD, Down’s syndrome, hereditary cerebral hemorrhage with amyloidosis, Dutch type (HCHWA-D), and cerebral infarction. CysC also co-localizes with Aβ amyloid deposits in the brains of non-demented aged individuals. Multiple lines of research show that CysC plays protective roles in AD. In vitro studies have shown that CysC binds Aβ and inhibits Aβ oligomerization and fibril formation. In vivo results from the brains and plasma of Aβ-depositing transgenic mice confirmed the association of CysC with the soluble, non-pathological form of Aβ and the inhibition of Aβ plaques formation. The association of CysC with Aβ was also found in brain and in cerebrospinal fluid from AD patients and non-demented control individuals. Moreover, in vitro results showed that CysC protects neuronal cells from a variety of insults that may cause cell death, including cell death induced by oligomeric and fibrillar Aβ. These data suggest that the reduced levels of CysC manifested in AD contribute to increased neuronal vulnerability and impaired neuronal ability to prevent neurodegeneration. This review elaborates on the neuroprotective roles of CysC in AD and the clinical relevance of this protein as a therapeutic agent.